QUALITY OF SERVICE USE COMMUNITY HEALTH INSURANCE (JAMKESMAS at BP RSUD Pringsewu LAMPUNG) - Bachtra Triansyah; Fitriyah .; Wiwik Widayati (Journal of Politic and Government Studies, 2014)
This research entitled " QUALITY OF SERVICE USE COMMUNITY HEALTH INSURANCE (JAMKESMAS at BP RSUD Pringsewu LAMPUNG).  BP RSUD Pringsewu is a government hospital at Pringsewu Regency and become one of health service provider in Health Insurance program.Problem identification in this research is how to healthcare services and perceptions of the service users .Descriptive qualitative method was use in this research and located at BP RSUD Pringsewu. Accidental and purposive sampling technique was use to choose the informant. Interactive analysis method was use to analyze the data. Key words: Jamkesmas, service